Pengaruh Beban Kerja, Kualitas Kerja, dan Pengembangan Karir Terhadap Kinerja Karyawan Pada PT. RPN Pusat Penelitian Kelapa Sawit Medan - Innayah; Yayuk, Yuliana; Anggia Sari, Lubis; Julianto, Hutasuhut (Jurnal Akutansi Manajemen Ekonomi Kewirausahaan (JAMEK), 2025)
This study aims to analyze the influence of workload, work quality, and career development on employee performance at PT.RPN Medan Palm Oil Research Center. The method used is a quantitative approach with an associative research type. Primary data was obtained through distributing questionnaires to 71 respondents, which were analyzed using multiple linear regression with the help of SPSS version 29. The results of the partial test (t test) showed that workload did not have a significant effect on employee performance (t = 0.347; sig. = 0.730 > 0.05). In contrast, work quality (t = 3.213; sig. = 0.002 < 0.05) and career development (t = 6.550; sig. < 0.001) had a positive and significant effect on employee performance. Simultaneously, the three independent variables together had a significant effect on employee performance (F = 50.143 > F table 2.74; sig. < 0.001). The coefficient of determination (R Square) value of 0.692 indicates that 69.2% of the variation in employee erformance can be explained by the variables of workload, work quality, and career development, while theremaining 30.8% is influenced by other factors outside this research model. This finding emphasizes the importance of work quality and career development in improving employee performance.